2021
DOI: 10.1088/1757-899x/1022/1/012110
|View full text |Cite
|
Sign up to set email alerts
|

Empirical analysis of regression techniques by house price and salary prediction

Abstract: Regression analysis is extensively used for prediction and prognostication, and its use has substantial overlap with the domain of machine learning. The main objective of this paper is to compare the performance of two regression techniques namely Simple Linear Regression (SLR) and Multiple Linear Regression (MLR) algorithms by two cases: predicting the salary of employees after certain years and predicting the prices of real estates. An employee’s salary depends on numerous factors, such as total employee exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…The above findings are consistent with economic expectations because an increase in the average gross salary increases purchasing power and the potential rise in residential property prices, whereas a surge in the interest rate on housing loans has the opposite effect. This conclusion is consistent with previously reported findings from other pertinent study in this area (Bansal, Narang, Sachdeva, Kashyap, & Panda, 2021), which revealed a significant relationship between changes in real estate prices and salaries. Serbia DOMex is statistically significant and influences the movement of the mean assessed residential real estate value per square meter in Serbia, according to regression statistics (Table 4).…”
Section: Gapsupporting
confidence: 94%
“…The above findings are consistent with economic expectations because an increase in the average gross salary increases purchasing power and the potential rise in residential property prices, whereas a surge in the interest rate on housing loans has the opposite effect. This conclusion is consistent with previously reported findings from other pertinent study in this area (Bansal, Narang, Sachdeva, Kashyap, & Panda, 2021), which revealed a significant relationship between changes in real estate prices and salaries. Serbia DOMex is statistically significant and influences the movement of the mean assessed residential real estate value per square meter in Serbia, according to regression statistics (Table 4).…”
Section: Gapsupporting
confidence: 94%
“…Martin et al analyzed machine learning methods to predict salary of employees that works in the field of information technology in Spain and they showed that the best accuracy, which is 84%, was obtained with decision tree algorithm [11]. Bansal et al compared simple linear regression and multiple linear regression to predict personnel salary and they showed that multiple linear regression was obtained better accuracy results [12]. Das et al designed a system to estimate personnel salary after specific time and they shared the visual results of that system [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bansal et al [2] study the comparison of two regression models in terms of performance. The two models chosen are multiple linear regression and linear regression with two specific scenarios in mind.…”
Section: Related Workmentioning
confidence: 99%